2007
DOI: 10.1007/s00453-007-9007-8
|View full text |Cite
|
Sign up to set email alerts
|

Cache-Oblivious R-Trees

Abstract: We develop a cache-oblivious data structure for storing a set S of N axisaligned rectangles in the plane, such that all rectangles in S intersecting a query rectangle or point can be found efficiently. Our structure is an axis-aligned bounding-box hierarchy and as such it is the first cache-oblivious R-tree with provable performance guarantees. If no point in the plane is contained in more than a constant number of rectangles in S, we can construct, for any constant ε, a structure that answers a rectangle quer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…A number of linear-space data structures have been proposed that achieve a query bound of O( √ N/B + K/B) block transfers in two dimensions and O((N/B) 1−1/d + K/B) block transfers in higher dimensions [9,19,20,22,26,28], where K is the number of reported points. The same bounds have been obtained in the cache-oblivious model [5,11]. In 2-d, Arge et al [8] showed that Θ(N log N/ log log B N) space is sufficient and necessary to obtain a query bound of O(log B N + K/B) block transfers for orthogonal range reporting in the I/O model.…”
Section: Related Worksupporting
confidence: 55%
“…A number of linear-space data structures have been proposed that achieve a query bound of O( √ N/B + K/B) block transfers in two dimensions and O((N/B) 1−1/d + K/B) block transfers in higher dimensions [9,19,20,22,26,28], where K is the number of reported points. The same bounds have been obtained in the cache-oblivious model [5,11]. In 2-d, Arge et al [8] showed that Θ(N log N/ log log B N) space is sufficient and necessary to obtain a query bound of O(log B N + K/B) block transfers for orthogonal range reporting in the I/O model.…”
Section: Related Worksupporting
confidence: 55%
“…Subsequently, a number of other results have been obtained in this model [1,5,6,7,10,11,12,13,14,17,18,19,20,28], among them several cacheoblivious B-tree structures with O(log B N ) search and update bounds [12,13,14,20,28]. Several of these structures also support one-dimensional range queries in O(log B N + T /B) memory transfers [13,14,20] (but at an increased update cost of O(log B N + 1 B log 2 2 N ) = O(log 2 B N ) amortized memory transfers).…”
Section: Previous Resultsmentioning
confidence: 94%
“…To date, representatives of capacity oblivious algorithms include matrix multiplication and transposition [17], funnel sort and distribution sort [12,17]. Representatives of block size oblivious algorithms are cache-oblivious B-trees [4,5,11] and Rtrees [3]. The cache-oblivious non-indexed NLJ we propose is capacity oblivious, and our indexed NLJ is both capacity oblivious and block size oblivious.…”
Section: Cache-conscious and Cache-oblivious Algorithmsmentioning
confidence: 98%
“…Since then, a few cache-oblivious algorithms and data structures [3,4,5,6,10,11,12,17] have been studied. The most interesting feature of this line of work is that, even though the model has no knowledge about the capacity and block size of each level of a multi-level memory hierarchy, a cache-oblivious algorithm has a provable upper bound on the number of block transfers for any two adjacent levels of the hierarchy.…”
Section: Introductionmentioning
confidence: 99%